Optimalisasi Aspek Asset Recovery Di Indonesia Dalam Perspektif Follow The Money - Muhammad Nurcholis Alhadi; Sutag Harsie; Muhammad Hanafi; Iranda Nadya Febianty (Jurnal Hukum Lex Generalis, 2026)
This research analyzes the legal construction of asset recovery in Indonesia from a follow the money perspective and formulates its optimization model. Findings show that the normative framework under the Anti-Corruption Law and the Anti-Money Laundering Law has not comprehensively accommodated non-conviction based confiscation. Regulatory fragmentation, the absence of an Asset Forfeiture Law, weak inter-agency coordination and international jurisdictional barriers are the main obstacles. The study recommends enactment of the Asset Forfeiture Bill, strengthening PPATK's pro justitia authority, optimizing mutual legal assistance and integrating big data and artificial intelligence in asset tracing as operational steps.